Automated fluorescent genotyping detects 10% of cryptic subtelomeric rearrangements in idiopathic syndromic mental retardation. Issue 4 (1st April 2002) - Rio, M; Molinari, F; Heuertz, S; Ozilou, C; Gosset, P; Raoul, O; Cormier-Daire, V; Amiel, J; Lyonnet, S; Le Merrer, M; Turleau, C; de Blois, M-C; et al.
Abstract : Recent studies have shown that cryptic unbalanced subtelomeric rearrangements contribute to a significant proportion of idiopathic syndromic mental retardation cases. Using a fluorescent genotyping based strategy, we found a 10% rate of cryptic subtelomeric rearrangements in a large series of 150 probands with severe idiopathic syndromic mental retardation and normal RHG-GTG banded karyotype. Fourteen children were found to carry deletions or duplications of one or more chromosome telomeres and two children had uniparental disomy. This study clearly shows that fluorescent genotyping is a sensitive and cost effective method that not only detects cryptic subtelomeric rearrangements but also provides a unique opportunity to detect uniparental disomies. We suggest giving consideration to systematic examination of subtelomeric regions in the diagnostic work up of patients with unexplained syndromic mental retardation.